Conjugated microporous polymer with visible light response and application thereof
By designing a specific structure, D-π-A conjugated microporous polymer and sodium perdisulfate, the photocatalytic degradation of perfluoro compounds is solved by using visible light, and the absorption wave of existing photocatalysts when degrading perfluoro compounds is solved. The problems of length and high energy consumption have achieved efficient and low energy consumption degradation effects.
Patent Information
- Application Number
- CN202411455645.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2024-12-27
AI Technical Summary
When existing photocatalysts degrade perfluoro compounds, they have short absorption wavelengths, strict reaction conditions and high energy consumption, making it difficult to effectively utilize visible light in solar energy, which limits the industrial application potential of photocatalytic methods.
A 2,4,6-tri(4-ethynylphenyl)-1,3,5-triazine and 2,6-dibromonaphthalene-1,5-diol were designed to be conjugated with π-conjugated Form-linked D-π-A type conjugated microporous polymer (CMP2-87) was synthesized by Sonogashira reaction and hydrothermal method, combined with sodium perdisulfate (PDS), and photocatalytic using 420nm-780nm visible light degradation.
It improves the utilization rate of visible light, significantly improves the adsorption and degradation efficiency of perfluoro compounds, and provides a green and efficient degradation method with good industrial application potential.
Smart Images

Figure BDA0005090374780000021 
Figure BDA0005090374780000071 
Figure BDA0005090374780000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conjugated microporous polymers, and in particular to a conjugated microporous polymer with visible light response and application thereof. Background Art
[0002] Conjugated microporous polymers (CMPs) are a class of emerging functional materials that are surrounded by a fully conjugated polymer network and have their own pore structure. They have a wide range of applications and their possibilities can be explored through molecular design and other means according to their application fields. CMPs have developed into emerging photoactive materials with their extended π-conjugated skeleton and rich porosity, and can be used as photocatalysts for the degradation of pollutants. However, for different pollutants, finding suitable photoactive units as donors (D) and acceptors (A) is the key to constructing D-π-A type CMPs with good photocatalytic activity.
[0003] Perfluorinated compounds such as perfluorooctanoic acid (PFOA) are bioaccumulative and toxic and have been widely detected in water bodies. Due to the stability of fluorides, conventional biodegradation methods in the water treatment industry cannot effectively degrade PFOA. Currently, the main methods for removing PFOA include adsorption, advanced oxidation, and photodegradation. Among them, the photocatalytic method is clean and efficient, low cost, and not prone to secondary pollution. It is one of the main research directions for removing PFOA in the future. Therefore, exploring suitable photocatalysts is a prerequisite for achieving photocatalytic degradation of perfluorinated compounds. At present, the commonly used photocatalysts for PFOA are mostly inorganic metal photocatalysts such as TiO2 doped with precious metals such as Pd-TiO2, which have high degradation efficiency, but there are still shortcomings such as short absorption wavelength of the photocatalyst (mainly ultraviolet light), harsh reaction conditions, and high energy consumption. If a new photocatalyst with good stability and high catalytic efficiency can be developed, it will have better application prospects. Summary of the invention
[0004] In order to make full use of visible light, which accounts for a higher proportion of solar energy, reduce reaction energy consumption and improve the potential of photocatalytic technology in industrial applications, the present invention designs a D-π-A type conjugated microporous polymer with a specific structure formed by alternating π-conjugated connection of units represented by formula I and units represented by formula II, which has visible light responsiveness and improves its utilization rate of visible light.
[0005] A conjugated microporous polymer with visible light response (denoted as: CMP2-87), which is formed by alternately connecting the units shown in formula I and the units shown in formula II in a π-conjugated form:
[0006]
[0007] The method for synthesizing the conjugated microporous polymer comprises: selecting 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine and 2,6-dibromonaphthalene-1,5-diol as building monomers, and preparing the conjugated microporous polymer by using an existing synthesis method of a conjugated microporous polymer or improving the existing synthesis method. Preferably, the method for synthesizing the conjugated microporous polymer comprises: synthesizing the conjugated microporous polymer CMP2-87 by using a Sonogashira reaction of 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine and 2,6-dibromonaphthalene-1,5-diol and using a hydrothermal method.
[0008] Preferably, the 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine and 2,6-dibromonaphthalene-1,5-diol can be fed in a molar ratio of 2:3.
[0009] The reaction is preferably completed under the catalysis of tetrakis(triphenylphosphine)palladium (Pd(PPh3)4) and cuprous iodide (CuI), which is more conducive to the reaction.
[0010] The reaction is preferably carried out in a solvent of dimethylformamide (DMF) and triethylamine (NEt3). Further preferably, the volume ratio of dimethylformamide to triethylamine is 2-3:1.
[0011] The reaction is preferably carried out under the protection of nitrogen or an inert gas.
[0012] The reaction conditions are preferably: 110° C.-130° C. for 22 h-26 h, and more preferably 120° C. for 24 h.
[0013] The reactants were filtered to obtain a solid, which was washed with water and methanol and then dried to obtain a conjugated microporous polymer CMP2-87.
[0014] The 2,6-dibromonaphthalene-1,5-diol in the present invention can be replaced by 2,6-diiodonaphthalene-1,5-diol substituted by other halogens such as iodine.
[0015] The conjugated microporous polymer can adsorb and / or degrade perfluorinated compounds, and can be used as a perfluorinated compound adsorbent material and / or a perfluorinated compound degradant, and can also be used to prepare a perfluorinated compound adsorbent material and / or a perfluorinated compound degradant. Preferably, the perfluorinated compound degradant is a degradant that uses visible light for photocatalytic degradation. Further preferably, the perfluorinated compound degradant comprises the conjugated microporous polymer and sodium persulfate.
[0016] The molar ratio of the unit represented by formula I to the unit represented by formula II in the conjugated microporous polymer is 2:3.
[0017] The conjugated microporous polymer can be used for adsorbing and / or degrading perfluorinated compounds, for example, can be used for adsorbing and / or degrading perfluorinated compounds in water.
[0018] The method for adsorbing perfluoro compounds by the conjugated microporous polymer comprises: uniformly mixing the conjugated microporous polymer with a solution containing perfluoro compounds (such as water) to complete the adsorption of perfluoro compounds by the conjugated microporous polymer. Preferably, the mixing time is greater than or equal to 10 minutes. Further preferably, the mixing time is greater than or equal to 10 minutes and less than or equal to 90 minutes. Most preferably, the mixing time is greater than or equal to 10 minutes and less than or equal to 60 minutes; generally, the adsorption equilibrium is basically reached in 60 minutes, and further increasing the mixing time has no significant effect on the adsorption effect. The appropriate adsorption time can be selected according to the field of application. Preferably, the amount of the conjugated microporous polymer used is at least 2 mg per 1 mg of perfluoro compound; further preferably, at least 10 mg of the conjugated microporous polymer is used per 1 mg of perfluoro compound; most preferably, 10 mg-20 mg of the conjugated microporous polymer is used per 1 mg of perfluoro compound; further increasing the amount used has no significant effect on the adsorption effect.
[0019] The conjugated microporous polymer is used in combination with sodium peroxydisulfate (i.e., sodium persulfate, PDS) for photocatalytic degradation of perfluoro compounds. The application method comprises: mixing the conjugated microporous polymer with a solution containing a perfluoro compound, adding sodium peroxydisulfate, and irradiating the solution with 420nm-780nm visible light to degrade the perfluoro compound. Alternatively, the application method comprises: mixing the conjugated microporous polymer with a solution containing a perfluoro compound, adsorbing it in the dark, adding sodium peroxydisulfate, and irradiating the solution with 420nm-780nm visible light to degrade the perfluoro compound. Preferably, the time for irradiating the solution with visible light is greater than or equal to 1min. Further preferably, the time for irradiating the solution with visible light is 1min-60min. Most preferably, the time for irradiating the solution with visible light is 20min-30min, and further increasing the irradiation time has no significant effect on the degradation effect. Preferably, for every 0.1mg of perfluoro compound, the amount of the conjugated microporous polymer used is at least 1mg, and the amount of the sodium peroxydisulfate used is at least 29.75mg. Further preferably, for every 0.1 mg of perfluoro compound, the amount of the conjugated microporous polymer used is 1 mg-2 mg, and the amount of the sodium persulfate used is at least 59.5 mg. Increasing the amount used has no significant effect on the degradation effect. The light-proof adsorption time is preferably greater than or equal to 10 min, more preferably greater than or equal to 10 min and less than or equal to 90 min, and most preferably greater than or equal to 10 min and less than or equal to 60 min.
[0020] The solution containing perfluorinated compounds can be water containing perfluorinated compounds.
[0021] The perfluorinated compound described in the present invention is one or more of perfluorooctanoic acid, sodium perfluorooctanoate, etc.
[0022] The activation mechanism of the CMPs of the present invention for persulfate is as follows: 1) Under the irradiation of visible light, the electrons in the HOMO orbit of the material absorb light of the corresponding wavelength and then transition to the LUMO orbit, generating photogenerated carriers and migrating to the surface of the photocatalytic material; 2) A part of the photogenerated electrons that transition to the LUMO orbit react with the persulfate, O2, etc. adsorbed on the surface of the material to generate oxidative sulfate free radicals SO4 ·– and superoxide anion O2 ·– The photogenerated holes generated by the electrons in the HOMO orbit of the material after the transition are oxidizing (the holes are required to have a higher potential) and can directly react with H2O or - OH reacts to generate ·OH; at the same time, some of the photogenerated electrons will recombine with the photogenerated holes and lose their activity; 3) SO4 generated by the material after light exposure ·– 、O2 ·– Active intermediates such as ·OH react with perfluorinated compounds and / or their anions adsorbed on the surface of materials, etc., converting them into small molecular compounds or even mineralizing them into CO2, H2O and NO x And other inorganic substances.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] The D-π-A type conjugated microporous polymer of the specific structure of the present invention has visible light responsiveness. It has adsorption and / or degradation effects on perfluoro compounds, especially perfluorooctanoic acid, sodium perfluorooctanoate, etc., and can be used as a perfluoro compound adsorption material or an adsorption material for preparing perfluoro compounds and applied to the fields of adsorption, separation, detection, etc.; it can also be used as a perfluoro compound visible light photocatalytic degradation agent or a visible light photocatalytic degradation agent for preparing perfluoro compounds, and applied to the fields of pollutant degradation. The CMPs / PDS synergistic photocatalytic degradation system composed of the conjugated microporous polymer of the specific structure of the present invention and PDS has a synergistic effect in the visible light photocatalytic degradation of perfluoro compounds, and utilizes the excellent adsorption performance, efficient photogenerated charge generation efficiency and high oxidizability of sulfate radicals of the CMPs of the specific structure of the present invention to improve the degradation activity of CMPs / PDS. Electron paramagnetic resonance (EPR) experiments show that the CMPs of the specific structure of the present invention can effectively activate PDS to generate sulfate radicals in situ under visible light irradiation, and the sulfate radicals will react with hydroxyl groups to generate a large number of hydroxyl radicals for the degradation of perfluoro compounds such as PFOA. The CMPs / PDS synergistic photocatalytic degradation system of the present invention provides a green, efficient and low-energy method for the degradation of perfluorinated compounds such as PFOA under visible light, and has good industrial application potential.
[0025] The D-π-A type conjugated microporous polymer with a specific structure of the present invention is used as a photocatalyst. The built-in electric field is constructed through the interaction between the donor (D) and the acceptor (A) with a specific structure, and the intersystem crossing of the photogenerated charges is promoted to improve the separation efficiency of the photogenerated charges of the material. At the same time, the electronic "push-pull" effect between D and A can also reduce the band gap E of the material. g , causing the absorption wavelength to red-shift and improving the material's utilization of visible light. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope (SEM) image of CMP2-87 of the present invention at a resolution of 300 nm;
[0027] Figure 2 This is a SEM image of CMP2-87 of the present invention at a resolution of 1 μm;
[0028] Figure 3 This is a SEM image of CMP2-87 of the present invention at a resolution of 10 μm;
[0029] Figure 4 is the EDS spectrum of CMP2-87 of the present invention;
[0030] Figure 5 is the infrared spectra of the monomer of the present invention and CMP2-87;
[0031] Figure 6This is a diagram showing the adsorption effect of CMP2-87 of the present invention on PFOA;
[0032] Figure 7 This is a diagram showing the adsorption and photocatalytic degradation effect of PFOA by the combination of CMP2-87 and PDS of the present invention;
[0033] Figure 8 This is a diagram showing the direct photocatalytic degradation effect of PFOA by combining CMP2-87 and PDS of the present invention;
[0034] Fig. 9 This is a photocatalytic degradation effect diagram of sodium perfluorooctanoate (20 mg / L) by combining CMP2-87 and PDS of the present invention;
[0035] Fig.10 The experimental effect diagram of photocatalytic degradation of PFOA in CMP2-87 combined with PDS group, CMP2-87 group, PDS group and blank control group; CMP2-87+PDS_25mM means that 4mg CMP2-87 and 25mM PDS were added at the same time in the photocatalytic degradation experiment, CMP2-87 means that only 4mg CMP2-87 was added, PDS_25mM means that only 25mM PDS was added, and No CMP2-87and PDS_25mM means that neither CMP2-87 nor PDS was added;
[0036] Fig.11 This is a diagram showing the adsorption and degradation effects of the CMP2-87 of the present invention when it is reused;
[0037] Fig.12 The performance comparison effect diagram of three photocatalytic degradation systems composed of CMP2-87 of the present invention and common photocatalysts TiO2 and g-C3N4 (graphene carbon nitride) respectively with PDS for PFOA degradation;
[0038] Fig.13 is the infrared spectra of the monomer and CMP2-108 in Comparative Example 2;
[0039] Fig.14 The photocatalytic degradation effect of CMP2-87 and its analogue CMP2-108 in combination with PDS on PFOA;
[0040] Fig.15 The kinetics of the degradation of PFOA by photocatalytic degradation of PFOA by CMP2-87 of the present invention is shown in the figure, wherein the ordinate varies according to the reaction order. For a zero-order reaction, the ordinate is the initial PFOA concentration C0 and the PFOA concentration C in the solution at time t. t For a first-order reaction, the ordinate is the initial PFOA concentration C0 and the PFOA concentration C in the solution at time t. tThe natural logarithm of the ratio (ln(C0 / C t )); For a secondary reaction, the ordinate is the difference between the reciprocal of the concentration of PFOA in the solution at time t and the reciprocal of the initial concentration (1 / C t -1 / C0);
[0041] Fig.16 The diagram is a diagram of the activation mechanism of persulfate by using CMPs as a photocatalyst in the present invention;
[0042] Fig.17 This is the EPR test result of CMP2-87 and PDS aqueous solution after visible light irradiation;
[0043] Wherein, Wavenumber represents the wave number, Time(min) represents the time(minutes), C t / C0(%) represents the concentration of perfluorinated compounds in the solution at different times C t The percentage of the initial concentration C0 of perfluorinated compounds in the solution, c (mg / L) represents the concentration of perfluorinated compounds in the solution, Time of visible light exposure represents the visible light exposure time, h represents hours, min represents minutes, Dark represents light-proof environment, Light on represents light environment, Run represents the number of uses, Field / G represents the magnetic induction intensity (G), and Intensity / au represents the response intensity (au). DETAILED DESCRIPTION
[0044] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand the technical solutions of the present invention.
[0045] The conditions for the visible light photocatalytic degradation experiment using a xenon lamp to simulate natural light include: using a xenon lamp to simulate the visible light wave of 420nm-780nm in natural light, the lamp power is 400W, the light power at the reaction tube is 4.10mW, and the light power density is 5.35mW / cm 2 .
[0046] Example 1
[0047] Based on the Sonogashira reaction, CMPs were synthesized by hydrothermal synthesis: 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine (76.1 mg, 0.2 mmol), 2,6-dibromonaphthalene-1,5-diol (96.2 mg, 0.3 mmol), tetrakis(triphenylphosphine)palladium (Pd(PPh3)4, 1.5 mg, 0.001 mmol, added at 0.5% of the mol amount of 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine) and cuprous iodide (CuI, 0.8 mg, 0.004 mmol, added at 2% of the mol amount of 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine) were weighed into the inner lining of a hydrothermal reactor, and then 4 mL of dimethylformamide (DMF) and 2 mL of triethylamine (NEt3) solvent were added. Mix well and evacuate for 2 min before filling with N2. The liner was then ultrasonicated for 3 minutes to remove the air in the solvent. After repeated ventilation (N2) twice, the liner was placed in the reactor and tightened, and then the reactor was placed in an oven preheated to 120°C for 24 hours. After the reactor was cooled to room temperature, the reactor was opened to obtain a black jelly-like solid. 20 mL of water was added and stirred with a magnetic stirrer for 3 minutes, then filtered. The solid was washed twice with 20 mL of water and twice with 20 mL of methanol. The solid was collected in the liner, 20 mL of methanol was added and ultrasonicated for 3 minutes, then filtered and washed twice with an appropriate amount of methanol. The solid was dried in a vacuum drying oven at 80°C for 6 hours to obtain the target product. Finally, an agate mortar was used to grind the product into powder for use, recorded as CMP2-87; SEM images of the material at different resolutions are shown in Figure 1-Figure 3 , the EDS spectrum of the material is shown in Figure 4 .
[0048] The SEM images of the material of the present invention at different resolutions show that: the overall picture of the material is shown at a resolution of 1.0 μm, and it can be seen that CMP2-87 is a porous structure as a whole, with pore sizes of different sizes and relatively large pore sizes. The SEM image at a resolution of 300 nm shows that the surface of the material is uneven, and there are many smaller pores around the large pores and on the surface of the material. This porous structure provides the basis for the excellent adsorption performance of the material.
[0049] The EDS spectrum shows that the surface of the material of the present invention mainly contains C, N, O, and Br (the weight percentages are 76.8%, 12.7%, 5.6%, and 4.9%, respectively, and Br is considered to be a small amount of Br in the raw material that has not been completely reacted), and the contents of Pd and Cu that are generally believed to have an activation effect on PDS are both 0. This shows that the activation of PDS by the material of the present invention is achieved by the unique conjugated structure of the CMPs material of the present invention itself under visible light irradiation, rather than the transition metals Pd and Cu that may be introduced during the synthesis process.
[0050] The infrared spectra of monomer and CMP2-87 are shown in Figure 5 As shown, 3240cm -1 and 3290cm -1 The absorption peak near 666cm is attributed to the vibration peak of the CH bond in the terminal alkyne in the monomer 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine, which disappears in CMP2-87; -1 The absorption peak nearby is attributed to the vibration peak between C-Br in the monomer 2,6-dibromonaphthalene-1,5-diol. This peak is not obvious in CMP2-87 and is significantly weaker than that in 2,6-dibromonaphthalene-1,5-diol, indicating that most of the C-Br bonds in CMP2-87 have disappeared and only a small amount of incompletely reacted C-Br bonds exist; combined with the infrared spectra of the monomer 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine, the monomer 2,6-dibromonaphthalene-1,5-diol and CMP2-87, it shows that CMP2-87 has been successfully synthesized and is a conjugated microporous polymer formed by alternating π-conjugated forms of the units shown in formula I and the units shown in formula II.
[0051]
[0052] Example 2 Application of CMP2-87 in adsorption of PFOA
[0053] Adsorption performance
[0054] 50mL 10mg / L PFOA aqueous solution (0.5mg PFOA), add 10mg CMP2-87 (0.2g / L), stir at room temperature (300 rpm) for a certain period of time. The adsorption effect of CMP2-87 on PFOA is shown in Figure 6 .
[0055] Adsorption performance of the CMPs material of the present invention: adsorption has basically reached adsorption equilibrium in 1 hour, and a maximum of 43% of PFOA can be adsorbed; adsorption mainly occurs within the first 10 minutes, and basically 25% of PFOA can be adsorbed. The maximum adsorption capacity is 21.5 mg / g. It can be seen that the CMPs material CMP2-87 of the present invention can be used as an adsorption material for perfluorooctanoic acid and other perfluoro compounds or for preparing adsorption materials for perfluorooctanoic acid and other perfluoro compounds, and applied to the fields of adsorption, separation, and detection.
[0056] Example 3 Adsorption and photocatalytic degradation performance of CMP2-87 combined with PDS
[0057] Photocatalytic degradation conditions: 4 mg CMP2-87 was placed in a 100 mL quartz reaction tube, 20 mL of 10 mg / L PFOA aqueous solution (PFOA 0.2 mg, CMP2-87 concentration 0.2 g / L) was added and placed in a photoreactor. After 1 h away from light, PDS was added (the final concentration of PDS was 25 mmol / L) and a xenon lamp equipped with a filter was turned on. The xenon lamp was used to simulate natural light to start the visible light photocatalytic degradation experiment. The effect is shown in Figure 2. Figure 7 .
[0058] Photocatalytic degradation effect:
[0059] The initial PFOA concentration in the PFOA aqueous solution was 10 mg / L. After 1 hour of exposure to light, the PFOA concentration was 5.9 mg / L. After 0.5 hours of exposure to visible light, the PFOA concentration dropped rapidly from 5.9 mg / L to 0.5 mg / L. The visible light photocatalytic degradation rate reached 54%, and the apparent degradation rate was 10.8 mg·L -1 ·h -1 (0.026mmol·L -1 h -1 ).
[0060] Example 4 Photocatalytic degradation performance of PFOA by combining CMP2-87 with PDS
[0061] Photocatalytic degradation conditions: Take 4 mg CMP2-87 in a 100 mL quartz reaction tube, add 20 mL 10 mg / L PFOA aqueous solution (PFOA 0.2 mg, CMP2-87 concentration 0.2 g / L) and place in a photoreactor, directly add PDS (the final concentration of PDS is 25 mmol / L) and turn on the xenon lamp equipped with a filter to simulate natural light to start the visible light photocatalytic degradation experiment. The photocatalytic degradation effect is shown in Figure 8 .
[0062] After 1 minute of illumination, the concentration of PFOA decreased rapidly from 10.0 mg / L to 7.5 mg / L, the visible light photocatalytic degradation rate reached 25%, and the apparent degradation rate was 150 mg·L -1 ·h -1 (0.36mmol·L -1 ·h -1 After 5 minutes of illumination, the concentration of PFOA decreased from 10.0 mg / L to 4.4 mg / L, the visible light photocatalytic degradation rate reached 56%, and the apparent degradation rate was 67.2 mg·L -1 ·h -1 (0.16mmol·L -1 ·h -1). After 10 minutes of illumination, the concentration of PFOA decreased from 10.0 mg / L to 2.0 mg / L, and the visible light photocatalytic degradation rate reached 80%. After 15 minutes of illumination, the concentration of PFOA decreased from 10.0 mg / L to 0.8 mg / L, and the visible light photocatalytic degradation rate reached 92%. Extending the illumination time to 20 minutes, the concentration of PFOA decreased to 0.6 mg / L, and the visible light photocatalytic degradation rate reached 94%. Although the degradation rate increases with the increase of illumination time, the increase in the later period is very limited after the initial degradation is completed.
[0063] The total organic carbon (TOC) in the solution after illumination in the CMP2-87+PDS system was measured by a total organic carbon (TOC) analyzer, and the mineralization rate was calculated. The mineralization rate was 16% after 1 hour of illumination, and the mineralization rate was significantly increased to 39% after continuing to illuminate for 1 hour, which is an excellent performance. If the illumination time is increased, the mineralization efficiency of the reaction can be further improved.
[0064] The photocatalytic degradation kinetics was studied by using the zero-order kinetic model (C0-C t = k0t), first-order kinetic model (ln(C0 / C t )=k1t) and the second-order kinetic model (1 / C t –1 / C0=k2t) to fit the degradation kinetic data (where C t is the concentration of PFOA in the solution at time t, C0 is the initial concentration of PFOA, t is the illumination time, k0, k1, k2 are the corresponding reaction rates). For specific results, see Fig.15 :The degradation of PFOA in solution by CMP2-87 / PDS is a first-order reaction (the R of the fitted line is 2 The reaction rate is about 0.1416min -1 (or 8.5h -1 ).
[0065] It can be seen that the CMPs material CMP2-87 of the present invention, as a visible light photocatalytic degradation agent for perfluorooctanoic acid and other perfluoro compounds, or the visible light photocatalytic degradation agent for perfluorooctanoic acid and other perfluoro compounds prepared by CMP2-87, when used in combination with PDS, has a significant degradation effect on perfluorooctanoic acid and other perfluoro compounds, and can be applied to the field of pollutant degradation.
[0066] Example 5 Photocatalytic degradation performance of sodium perfluorooctanoate by combining CMP2-87 with PDS
[0067] Photocatalytic degradation conditions: Take 4 mg of CMP2-87 in a 100 mL quartz reaction tube, add 20 mL of 20 mg / L sodium perfluorooctanoate aqueous solution (sodium perfluorooctanoate 0.4 mg, CMP2-87 concentration 0.2 g / L), place in a photoreactor, directly add PDS (the final concentration of PDS is 25 mmol / L) and turn on the xenon lamp equipped with a filter to simulate natural light to start the visible light photocatalytic degradation experiment. The photocatalytic degradation effect is shown in Fig. 9 .
[0068] After 10 minutes of illumination, the concentration of sodium perfluorooctanoate decreased rapidly from 20.0 mg / L to 3.6 mg / L, the visible light photocatalytic degradation rate reached 82%, and the apparent degradation rate was 98.4 mg·L -1 ·h -1 (0.23mmol·L -1 ·h -1 After 30 minutes of illumination, the concentration of sodium perfluorooctanoate decreased from 20.0 mg / L to 1.5 mg / L, the visible light photocatalytic degradation rate reached 92.5%, and the apparent degradation rate was 37 mg·L -1 ·h -1 (0.09mmol·L -1 ·h -1 ). After 60 minutes of illumination, the concentration of sodium perfluorooctanoate decreased from 20.0 mg / L to 1.2 mg / L, and the visible light photocatalytic degradation rate reached 94%.
[0069] The CMPs material CMP2-87 of the present invention can be used as a visible light photocatalytic degradation agent for perfluoro compounds such as sodium perfluorooctanoate or used to prepare a visible light photocatalytic degradation agent for perfluoro compounds such as sodium perfluorooctanoate. When used in combination with PDS, it has a significant degradation effect on perfluoro compounds such as perfluorooctanoic acid and is applied to the degradation of pollutants and other fields.
[0070] Example 6 Photocatalytic degradation performance of CMP2-87 combined with PDS
[0071] Photocatalytic degradation conditions: Take 4 mg CMP2-87 in a 100 mL quartz reaction tube, add 20 mL 10 mg / L PFOA aqueous solution (PFOA 0.2 mg, CMP2-87 concentration 0.2 g / L) and place in a photoreactor, directly add PDS (the final concentration of PDS is 25 mmol / L) and turn on the xenon lamp equipped with a filter to simulate natural light to start the visible light photocatalytic degradation experiment. The photocatalytic degradation effect is shown in Fig.10 .
[0072] After 10 minutes of illumination, the concentration of PFOA decreased from 10.0 mg / L to 2.2 mg / L, the visible light photocatalytic degradation rate was 78%, and the apparent degradation rate was 46.8 mg·L -1 ·h -1 (0.11mmol·L -1 ·h -1 After 60 minutes of illumination, the concentration of PFOA decreased from 10.0 mg / L to 0.3 mg / L, and the visible light photocatalytic degradation rate was 97%.
[0073] Photocatalytic degradation performance of PDS
[0074] Photocatalytic degradation conditions: Take 20mL of 10mg / L PFOA aqueous solution and 250μL of 2mol / LPDS (the final concentration of PDS is 25mmol / L) in a 100mL quartz reaction tube, then place it in a photoreactor, turn on the xenon lamp equipped with a filter, and use the xenon lamp to simulate natural light to start the visible light photocatalytic degradation experiment. The photocatalytic degradation effect is shown in Fig.10 .
[0075] After 10 minutes of illumination, the concentration of PFOA decreased from 10.0 mg / L to 9.0 mg / L, the visible light photocatalytic degradation rate was only 10%, and the apparent degradation rate was 6.0 mg·L -1 ·h -1 (0.014mmol·L -1 ·h -1 After 60 minutes of illumination, the concentration of PFOA was still 9.0 mg / L, the visible light photocatalytic degradation rate was 10%, and the apparent degradation rate was 1.0 mg·L -1 ·h -1 (0.002mmol·L -1 ·h -1 ), it can be seen that visible light has no obvious activation effect on PDS.
[0076] Photocatalytic degradation performance of CMP2-87
[0077] Photocatalytic degradation conditions: Take 4 mg CMP2-87 in a 100 mL quartz reaction tube, add 20 mL 10 mg / L PFOA aqueous solution (PFOA 0.2 mg, CMP2-87 concentration 0.2 g / L) and place in a photoreactor, turn on the xenon lamp equipped with a filter, and use the xenon lamp to simulate natural light to start the visible light photocatalytic degradation experiment. The photocatalytic degradation effect is shown in Fig.10 .
[0078] After 10 minutes of illumination, the concentration of PFOA decreased from 10.0 mg / L to 9.4 mg / L, the visible light photocatalytic degradation rate was only 6%, and the apparent degradation rate was 3.6 mg·L-1 ·h -1 (0.009mmol·L -1 ·h -1 After 60 minutes of illumination, the concentration of PFOA decreased from 10.0 mg / L to 7.2 mg / L, the visible light photocatalytic degradation rate was 28%, and the degradation rate was 2.8 mg·L -1 ·h -1 (0.007mmol·L -1 ·h -1 ).
[0079] Blank control group: photocatalytic degradation performance of PFOA by visible light
[0080] Photocatalytic degradation conditions: Take 20mL of 10mg / L PFOA aqueous solution in a 100mL quartz reaction tube and place it in a photoreactor, turn on the xenon lamp equipped with a filter, and use the xenon lamp to simulate natural light to start the visible light photocatalytic degradation experiment. The photocatalytic degradation effect is shown in Fig.10 .
[0081] After 10 minutes of illumination, the concentration of PFOA decreased from 10.0 mg / L to 9.8 mg / L, the visible light photocatalytic degradation rate was only 2%, and the apparent degradation rate was 1.2 mg·L -1 ·h -1 (0.003mmol·L -1 ·h -1 ). After 60 minutes of illumination, the concentration of PFOA was still 10.0 mg / L, and the visible light photocatalytic degradation rate was 0%. It can be seen that visible light of 420-780 nm cannot directly degrade PFOA.
[0082] Comparison of the CMP2-87 and PDS combined group, CMP2-87 group, PDS group, and blank control group shows that the degradation rate of PFOA by the CMP2-87 / PDS synergistic photocatalytic system under 1h of visible light irradiation reached 97%; when CMP2-87 alone was used, the degradation rate of PFOA was 28%; when PDS alone was used, the degradation rate of PFOA was 10%; visible light had almost no degradation effect on PFOA. The degradation efficiency of PFOA by the CMP2-87 / PDS synergistic photocatalytic degradation system (97%) is not only much higher than the efficiency of using CMP2-87 alone and PDS alone (28% and 10%, respectively), but also much higher than the sum of the efficiencies of the two when used alone (38%), indicating that there is a very obvious synergistic effect between CMP2-87 and PDS, achieving the effect of "1+1>2". It can be seen that CMP2-87 responds to visible light and can activate PDS to a certain extent for the degradation of perfluorinated compounds such as PFOA. The combination of CMP2-87 and PDS has a synergistic effect on the visible light catalytic degradation of PFOA.
[0083] Example 7 Recyclability of Materials
[0084] Photocatalytic degradation experiment: Take 12 100mL quartz reaction tubes, add 4mg CMP2-87 and 20mL 20mg / L perfluorooctanoic acid aqueous solution (perfluorooctanoic acid 0.4mg, CMP2-87 concentration 0.2g / L) respectively, and place in a photoreactor. After avoiding light for 1h, add PDS (so that the final concentration of PDS is 25mmol / L) and turn on the xenon lamp equipped with a filter. Use the xenon lamp to simulate natural light to start the visible light photocatalytic degradation experiment. Samples were taken after avoiding light for 1h and after a certain period of light exposure, and the concentration of PFOA in the solution was detected using a liquid chromatography-mass spectrometer. After the experiment, the test tube was taken out, and the reacted CMP2-87 material was filtered (washed with deionized water and methanol in turn) and recovered. Then it was dried in a vacuum drying oven and used for the next cycle experiment.
[0085] The results of the cycling experiment on PFOA can be found in Fig.11 The results show that after four uses, the adsorption performance of the material CMP2-87 of the present invention has been reduced, and the adsorption rate has been reduced from 42% in the first use to 24% in the fourth cycle, but it still has a certain adsorption performance and can be used as a perfluorooctanoic acid adsorption material or an adsorption material for preparing perfluorooctanoic acid and applied to adsorption, separation, detection and other fields; but the photocatalytic performance has not been significantly reduced, and the total elimination rate of perfluorooctanoic acid can still reach 84% within 30 minutes and 90% within 60 minutes. It can be used as a visible light photocatalytic degradation agent for perfluorooctanoic acid and other perfluoro compounds or a visible light photocatalytic degradation agent for preparing perfluorooctanoic acid and other perfluoro compounds and applied to the degradation of pollutants and other fields. It can be seen that the material CMP2-87 of the present invention has good reusability, which not only saves the cost of using materials in practical applications, but also conforms to the concept of environmental protection and energy saving.
[0086] Comparative Example 1
[0087] Photocatalytic degradation conditions: Weigh 4mg CMP2-87, 4mg g-C3N4 and 4mg TiO2 in 100mL quartz reaction tubes, add 20mL 10mg / L PFOA aqueous solution (PFOA 0.2mg, photocatalyst content 0.2g / L) and place in a photoreactor, add PDS (make the final concentration of PDS 25mmol / L) and turn on the xenon lamp equipped with a filter, use the xenon lamp to simulate natural light to start the visible light photocatalytic degradation experiment, take samples at a certain time of illumination, filter through a 0.45μm×13mm filter membrane to obtain the test solution. Measure 20μL of the test solution, 20μL of the internal standard (5mg / LPFOS aqueous solution, i.e., perfluorooctane sulfonate aqueous solution) and 960L of deionized water in a 2mL injection bottle, mix well and use a high performance liquid chromatography-mass spectrometer for testing. See the effect. Fig.12 .
[0088] The test results show that the common photocatalysts TiO2, g-C3N4 and PDS do not have obvious photocatalytic degradation of PFOA. After 1 hour of illumination, the total elimination rate of PFOA in the solution is no more than 10%. The CMP2-87 material has an excellent degradation effect, with a total elimination rate of 97%. It can be seen that TiO2 and g-C3N4 do not respond well to visible light, and cannot efficiently activate PDS to produce sulfate radicals for the degradation of perfluorinated compounds such as PFOA like CMP2-87 under visible light. Therefore, the material CMP2-87 of the present invention not only has good adsorption performance for perfluorinated compounds such as PFOA, but also has very obvious advantages over the common photocatalysts TiO2 and g-C3N4 in the photocatalytic degradation of perfluorinated compounds such as PFOA under visible light.
[0089] Comparative Example 2
[0090] The conjugated microporous polymer CMP2-108 was prepared by replacing "2,6-dibromonaphthalene-1,5-diol (96.2 mg, 0.3 mmol)" in Example 1 with "2,6-dibromonaphthalene (85.8 mg, 0.3 mmol)" and keeping the other steps the same as Example 1.
[0091] The infrared spectra of monomer and CMP2-108 are shown in Fig.13 As shown, 3240cm -1 and 3290cm -1 The absorption peak near 624cm is attributed to the vibration peak of the CH bond in the terminal alkyne in the monomer 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine, which disappears in CMP2-108; -1The absorption peak nearby is attributed to the vibration peak between C-Br in the monomer 2,6-dibromonaphthalene. This peak is not obvious in CMP2-108 and is significantly weaker than that in 2,6-dibromonaphthalene, indicating that most of the C-Br bonds in CMP2-108 have disappeared and only a small amount of incompletely reacted C-Br bonds exist; combined with the infrared spectra of the monomer 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine, the monomer 2,6-dibromonaphthalene and CMP2-108, it shows that CMP2-108 has been successfully synthesized and is a conjugated microporous polymer formed by alternating π-conjugated forms of the units shown in formula I and the units shown in formula III.
[0092]
[0093] CMP2-108 was used to replace CMP2-87 in Example 4, and other aspects were the same as in Example 4 to carry out a visible light photocatalytic degradation experiment.
[0094] Comparison of the degradation effects of CMP2-87 and CMP2-108 polymers on PFOA aqueous solution under visible light Fig.14 As shown: CMP2-87 can degrade 78% of PFOA within 10 minutes, while CMP2-108 can only degrade 16% of PFOA. After 60 minutes of illumination, the degradation rates of CMP2-87 and CMP2-108 are 97% and 17%, respectively. It can be seen that CMP2-87 has a very obvious advantage over CMP2-108 in the photocatalytic degradation of PFOA. By comparing the structure and performance of CMP2-87 and CMP2-108, it can be concluded that the specific structure of CMP2-87 and its hydroxyl group play an important role in improving the photocatalytic degradation of PFOA.
[0095] After 4 mg CMP2-108 was stirred and exposed to light for 60 min in a 20 mL 10 mg / L PFOA aqueous solution, the concentration of PFOA in the aqueous solution was only reduced by 17%. This shows that the adsorption performance of CMP2-108 for PFOA is also poor, lower than 43% of CMP2-87 (see Figure 6 ). In summary, the hydroxyl groups on the specific structure of the material of the present invention play a very important role in the adsorption and degradation of PFOA in aqueous solution by CMP2-87.
[0096] The activation mechanism of the CMPs of the present invention for persulfate can be found in Fig.16 :1) Under the irradiation of visible light, the electrons in the HOMO orbit of the material absorb the light of the corresponding wavelength and then jump to the LUMO orbit, generating photogenerated carriers and migrating to the surface of the photocatalytic material; 2) A part of the photogenerated electrons that jump to the LUMO orbit react with the persulfate, O2, etc. adsorbed on the surface of the material to generate oxidizing sulfate radicals SO4 ·–and superoxide anion O2 ·– The photogenerated holes generated by the electrons in the HOMO orbit of the material after the transition are oxidizing (the holes are required to have a higher potential) and can directly react with H2O or - OH reacts to generate ·OH; at the same time, some of the photogenerated electrons will recombine with the photogenerated holes and lose their activity; 3) SO4 generated by the material after light exposure ·– 、O2 ·– Active intermediates such as ·OH react with perfluorinated compounds and / or their anions adsorbed on the surface of materials, etc., converting them into small molecular compounds or even mineralizing them into CO2, H2O and NO x And other inorganic substances.
[0097] Weigh 4 mg of CMP2-87 into a 100 mL quartz reaction tube, add 20 mL of water and place in a photoreactor, add PDS (to make the final concentration of PDS 25 mmol / L) and turn on a xenon lamp equipped with a filter to simulate natural light. After irradiating the aqueous solution of CMP2-87 and PDS with visible light of 420 nm-780 nm, the EPR technology is used to directly detect active free radicals such as SO4·– and ·OH (hydroxyl radical) in the system. The test results are shown in Fig.17 (DMPO in the figure is 5,5-dimethyl-1-pyrroline-N-oxide): With the increase of illumination time, the relative concentration of ·OH in the solution increased significantly, while the content of SO4·– did not increase significantly. The inventors of the present invention believe that SO4·– and ·OH are indeed generated in situ in the system during illumination, and during the reaction, SO4·– will react with hydroxyl groups to generate ·OH. EPR experiments show that CMPs with a specific structure of the present invention can effectively activate PDS to generate sulfate radicals in situ under visible light irradiation. Sulfate radicals will react with hydroxyl groups to generate a large number of hydroxyl radicals for the degradation of perfluorinated compounds such as PFOA. The CMPs / PDS synergistic photocatalytic degradation system of the present invention provides a green, efficient and low-energy method for the degradation of perfluorinated compounds such as PFOA under visible light, and has certain industrial application potential.
Claims
1. A conjugated microporous polymer with visible light response, characterized in that: The units shown in formula I and the units shown in formula II are alternately connected in a π-conjugated form:
2. Use of the conjugated microporous polymer according to claim 1 as a perfluorinated compound adsorbent and / or a perfluorinated compound degrading agent.
3. Use of the conjugated microporous polymer according to claim 1 in preparing a perfluorinated compound adsorbent material and / or a perfluorinated compound degradation agent.
4. The use according to claim 2 or 3, characterized in that: The perfluorinated compound degradation agent is a perfluorinated compound visible light photocatalytic degradation agent.
5. Use of the conjugated microporous polymer according to claim 1 in the adsorption and / or degradation of perfluorinated compounds.
6. The use according to claim 5, characterized in that: The method for adsorbing a perfluorinated compound by a conjugated microporous polymer comprises: uniformly mixing the conjugated microporous polymer with a solution containing a perfluorinated compound.
7. The use according to claim 6, characterized in that: The mixing time is greater than or equal to 10 min.
8. The use according to claim 5, characterized in that: The conjugated microporous polymer is used in combination with sodium persulfate and uses visible light to photocatalytically degrade perfluorinated compounds.
9. The use according to claim 8, characterized in that: The application method comprises: mixing the conjugated microporous polymer with a solution containing a perfluorinated compound, adding sodium persulfate, and irradiating the solution with visible light of 420nm-780nm to degrade the perfluorinated compound; or, mixing the conjugated microporous polymer with a solution containing a perfluorinated compound, adsorbing the mixture in the dark, adding sodium persulfate, and irradiating the solution with visible light of 420nm-780nm to degrade the perfluorinated compound.
10. The use according to claim 9, characterized in that: The time for irradiating the solution with visible light is greater than or equal to 1 min.